The 28th SEA Games : media coverage of the extraordinary - Tay, Cassandra Hwee Min (2016)
With the advent of technology, it is important to understand the role of media coverage and the significance it places on sport performance development through the lens of a multi-sport games. Several studies have identified factors behind elite sporting success (Green and Houlihan, 2007; Digel, 2002a, b; Oakley and Green, 2001, 2001a) and evidence of media involvement in promotion and raising physical activity levels (Leavy, Bull, Rosenberg & Bauman, 2011) exists. However, little is known about the significance of media coverage on competitive sport development in the local context. This study seeks to understand the significance of media coverage specifically on volleyball in the 28th SEA Games and determine the importance of media in contributing to achieving elite sporting success of local sports. Three participants were selected through purposive sampling and interviews were conducted. Analysis of the data revealed significance of media coverage in three areas: (a) sparking interest in younger generation to increase talent pool, (b) a platform for emotional support, and (c) increase funding for the sport. It highlighted evidences of media coverage on volleyball during the games, however, the general lack in media coverage of the sport remains. Study findings suggest that media coverage provides a platform for achieving elite sporting success through raising awareness and promotion of the sport. It encourages public support and increasing fan base of the athletes.